PS02.220: ATTENUATION OF SATIETY GUT HORMONES INCREASES APPETITE AFTER CURATIVE ESOPHAGECTOMY FOR ESOPHAGEAL CANCER. (14th September 2018) - Elliott, Jessie; Docherty, Neil; Murphy, Conor; Eckhardt, Hans; Ravi, Narayanasamy; Le Roux, Carel; Reynolds, John
Abstract: Background: Reduced appetite and weight loss after esophagectomy (ES) occur in the context of an exaggerated postprandial satiety gut hormone response. Satiety gut hormones modulate central processing of food reward, resulting in reduced energy intake. The aim of this study was to investigate the effect of satiety gut hormone attenuation using the somatostatin analogue octreotide on appetitive behavior among patients after curative ES. Methods: In this randomized, double-blind, placebo-controlled crossover study, disease-free patients at least one year after ES with gastric conduit reconstruction and matched controls received either 1mL 0.9% saline or 1mL (100μg) octreotide subcutaneously, before completing a progressive ratio task (PRT). A measure of appetitive behavior, the PRT requires subjects to undertake progressively increasing amounts of work to obtain a reinforcer—the final completed increment (breakpoint) representing reinforcer reward value in different states. Separate cohorts were studied in the fasted or 1-hour postprandial states. The institutional Research Ethics Committee approved the study (REC 2015/21/02), which was registered on ClinicalTrials.gov prior to recruitment of the first participant (NCT02381249). Results: 36 subjects (ES, n = 18, matched controls, n = 18) were studied. 2.5 ± 0.3 years postoperatively, ES patients demonstrated 14.6 ± 2.6% weight loss and an elevated postprandial GLP-1 (49.2 ± 13.4 versus controls with 20.2 ± 2.3 pM, P = 0.038). Octreotide did not alter appetite among ES or control subjects when tested fasting (breakpoint, ES: 980 ± 371 versus 1700 ± 583, P = 0.16; control: 1056 ± 274 versus 1124 ± 273, P = 0.80). When tested one hour postprandially, octreotide was associated with increased appetitive behavior versus placebo among ES subjects (breakpoint, 322 ± 143 versus 246 ± 149, P = 0.037), but not controls (248 ± 119 versus 247 ± 120, P = 0.98). Conclusion: Attenuation of the exaggerated postprandial satiety gut hormone response is associated with increased appetitive behavior towards a sweet-fat stimulus among patients post ES. Suppression of satiety gut hormones may represent a novel target to increase appetite, food intake and body weight in patients after esophagectomy. Disclosure: All authors have declared no conflicts of interest.